Evaluation of Tp‐e Interval, Tp‐e/QT Ratio, and Tp‐e/QTc Ratio in Patients with Asymptomatic Arrhythmogenic Right Ventricular Cardiomyopathy. Issue 1 (28th March 2016) - Alizade, Elnur; Yesin, Mahmut; Yazicioğlu, Mehmet Vefik; Karaayvaz, Ekrem Bilal; Atici, Adem; Arslan, Şükrü; Avci, Anıl; Acar, Göksel; Tabakci, Mustafa; Izci, Servet; Pala, Selçuk
Abstract : Background: Arrhythmogenic right ventricular dysplasia (ARVD) is characterized by progressive replacement of ventricular myocytes with variable amounts of fibrous and adipose tissue. Several studies have suggested that the interval from the peak to the end of the electrocardiographic T wave (Tp‐e) may correspond to the transmural dispersion of repolarization and that increased Tp‐e interval and Tp‐e/QT ratio are associated with malignant ventricular arrhythmias. The aim of this study was to evaluate repolarization dispersion measured from the 12‐lead surface electrocardiogram (including Tp‐e interval, Tp‐e/QT, and Tp‐e/QTc ratio) in asymptomatic ARVD patients Methods: We selected 27 patients with asymptomatic ARVD and 27 age‐ and gender‐match young, healthy volunteers. Results: Tp‐e interval, Tp‐e/QT and Tp‐e/QTc ratio were also significantly higher in ARVD group compared to the control group (all P < 0.001). There were negative correlation between S global and Tp‐e, Tp‐e/QT, Tp‐e/QTc ration (r = −0.57, P = 0.02; r = −0.85, P = 0.02; r = −0.63, P < 0.01; respectively). There were also negative correlation between Sm global and Tp‐e, Tp‐e/QT, Tp‐e/QTc ration (r = −0.61, P < 0.01; r = −0.67, P < 0.01; r = −0.68, P < 0.01; respectively). Moreover, Em global were negative correlation between Tp‐e, Tp‐e/QT, and Tp‐e/QTc (r = − 0.64, P < 0.001, r = − 0.75, P < 0.01; r = −0, 69, P < 0.01; respectively) Conclusion: In conclusion, we have presented strong evidence suggesting that Tp‐e interval, Tp‐e/QT ratio, and Tp‐e/QTc ratio were increased in asymptomatic ARVD patients.